(untitled) (University of Khartoum Journal of Agricultural Sciences, 2023)
Experiments were conducted at Shambat Research Station,Agricultural Research Corporation, Khartoum North, to test the effect ofconcentrations and application methods of benzyladenine (BA), as a pre-budding treatment, on scion bud-break and shoot elongation of grapefruit(Citrus paradisi Macf. cv. “Redblush”). Nine- to twelve- months old sourorange (Citrus aurantium L.) seedlings were used as rootstock. Twoapplication methods of BA (foliar and soaking) were evaluated. Theresults showed that increasing BA concentration increased all parametersmeasured relative to the controls, irrespective of the application method.The highest percentage of bud-break, the largest number of leaves, thelongest scion shoots and the most growth rating values were obtainedwith soaking in 400 mg BA/litre treatment, compared with the control orthe lower or higher BA concentrations tested or plants treated with thefoliar application method. No significant differences were obtainedamong BA concentrations tested or application methods used on scionshoot length. However, soak application method gave high values for allparameters measured compared with the soak application method.Treatment duration had no effect on the efficiency of BA on bud break.